Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 1582433 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Plantae", { "or" : [ "Country is Myanmar", "Country is Thailand", "Country is Singapore", "Country is Lao People’s Democratic Republic", "Country is Viet Nam", "Country is Timor-Leste", "Country is Philippines", "Country is Indonesia", "Country is Malaysia", "Country is Brunei Darussalam", "Country is Cambodia" ] } ] } The dataset includes 1582433 records from 250 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000030-160311141623029/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences